Brown Rice - Manickavasagan, Annamalai; Santhakumar, Chandini; Venkatachalapathy, N. (Springer International Publishing : Imprint: Springer, 2017)
This book provides a broad-based foundation of knowledge about brown rice, including the latest information on health benefits and disease prevention resulting from consumption of brown rice, and information on consumer knowledge, attitudes, and behaviors towards brown rice. It is the first book of its kind to provide a comprehensive review of current brown rice science and technology, regulatory/policy issues, dietary intake, consumer interest and health promotion. The edited volume focuses on the latest developments in breeding varieties for high quality brown rice, varietal variations, defects, milling, cooking quality, eating quality, post-harvest management and methods to improve shelf life. Contributing authors address the physical, chemical, engineering, nutritional and glycemic qualities of brown rice in different chapters. Authors also discuss the physiological functions of brown rice in vivo and radical scavenging activity, emphasizing their importance to grow ers, technologists and consumers, and providing insight into future advances. This comprehensive collection benefits scientists, nutritionists, dieticians, diabetic educators, and professionals in the food industry. The information covered is valuable for food scientists and technologists working to develop new brown rice products and enhance the taste, quality, and health profile of brown rice.
Keywords: Chemistry.; Food -- Biotechnology.; Nutrition.; Agriculture.; Plant breeding.; elektronické knihy; electronic books